A novel fMRI paradigm suggests that pedaling-related brain activation is altered after stroke - Promjunyakul, Nutta-on; Schmit, Brian D.; Schindler-Ivens, Sheila M. (Frontiers in Human Neuroscience, 2015)
Reviewer 2's suggestion to add data to the abstract pushed us over the character limit. So, the abstract no longer fits here. The complete, revised abstract can be found in the manuscript file. We seek input from the editor as to whether to fulfill the reviewer's requests for data or to keep the abstract within the character limit. We are happy to do either.